Postorbital discard and chain of custody: The processing of artifacts returning to Earth from the International Space Station. (June 2022) - Walsh, Justin St P.; Gorman, Alice C.; Castaño, Paola
Abstract: Few items that comprise the material culture of the International Space Station ever return to Earth. Most are left on the station or placed on cargo resupply ships that burn up on atmospheric re-entry. This fact presents a challenge for archaeologists who use material culture as their primary evidence. Together with a sociologist, we observed the processes that have been developed by NASA contractors to handle and return items that come back to Earth on the Cargo Dragon vehicle. We observed two missions, CRS-13 and CRS-14, in January and May 2018, respectively, traveling to the locations of work and interviewing the contractors and associated staff. These observations are described here, using the lenses of archaeological understandings of discard practices, the anthropological concept of the chaîne opératoire, and the forensic idea of "chain of custody" to interpret the meanings and associations of the various kinds of objects returned from space. Highlights: Processes for handling cargo from ISS are elaborate, thorough, and costly. ISS cargo includes scientific samples, broken equipment, and crew personal items. Archaeology and sociology show the meanings behind ISS cargo processes.